Determining factors in the development of road freight transport - Kveiborg, Ole (Proceedings from the Annual Transport Conference at Aalborg University, 2000)
To answer the question: What are the determinants of the development in the freight transport? a model, linking the general economic development to the development in the freight transport, has been developed. The model consists of several intermediate steps, each linking one intermediate factor with the next, and each having a dynamic element being able to move the development away from the overall trend. The general driving factors are the economic growth in 19 different production sectors in the (Danish) economy (imports are also included). The production values in these sectors are linked to the production of 23 goods categories measured in weight terms (tonnes). The analysed determinants for these developments are competitive prices in the goods production sectors, and some technological trends. The crucial element in the model is the linking of the production in tonnes to the transport measured as tonnes, usually termed: The handling factor. The handling factor can be interpreted as an indicator of the structure of the production chains in an economy. Changes in the handling factor is due to changes in the location of the factories, centralised and decentralised production plants, more/fewer subcontractors, changes in the transport prices etc. In general this factor is decreasing due to one or more of the above mentioned influencing elements. However, in the model only price differences between the transport sector and the production sectors are used. These are used as proxy variables for all the above-mentioned influencing factors. The amount of transport – the traffic performance – is developed through a dynamic calculation of the average length of transport and of the average load of each transport disaggregated on the different goods categories. Again transport prices play an important role in the development of these two factors. The final outcome of the model is a calculation of the environmental impacts of the predicted development in the freight transport. The impacts are calculated as energy consumption, CO2, SO2 and NOX emissions. Having these measures as the overall target of the model, the model can be used as an indication of the sustainability of different economic changes proposed in the political system, and evaluated in general macro-economic model systems. One such model system is a Danish macro-economic model ADAM, used for evaluation of e.g. the Budget, and other proposals of fiscal changes. To be able to estimate the different intermediate links, two primary datasets have been used. One dataset with information on the production in 19 different production sectors and 23 different goods categories, measured both in fixed prices and in tonnes. The second dataset consists of information gathered in an annual transport survey of the freight transport on lorries in Denmark. This dataset contains information on the length of haul, the weight of the haul in the goods categories, and on different lorry sizes. Both datasets covers the period from 1980 to 1992. The data is used in standard time series estimations. The paper presents the model, and discusses the different (mainly macro-economic) impacts on the different elements in the model, and finally presents some examples of calculations that can be made with the model. However, the primary interest is on the model development, and the discussion of the possibilities of describing developments in the freight transport as a consequence of the development in the economic sectors.